Implementation of Arabic Karuta to Improve the Student’s Arabic Vocabularies in the Elementary School of Muhammadiyah Kauman - Dalila Nadya Pratama; Muh Naim Madjid; Zawawi bin Ismail (PPPBA, 2024)
The purpose of this study is to determine the outcomes of the design and implementation of karuta media for learning Arabic vocabulary among fifth-grade students at Kauman Muhammadiyah Elementary School. This form of research is known as research and development or R&D, and follows the D4 paradigm of defining, designing, developing, and distributing. The research methodology adopted is descriptive quantitative. The sample employed in this study was the full population of class V Students at Kauman Muhammadiyah Elementary School, which included three classes totaling 58 people. The cluster sampling approach was used to conduct the sampling. The research tools were a posttest and a pretest. Based on the Dependent Sample Test results, the significance level was 0.000, which is less than 0.05. Based on the findings of this study, it was determined that was rejected due to considerable variations from the outcomes of implementing karuta media. The pretest resulted in a mean of 58.10, while the posttest yielded 71.72. These results demonstrate that Karuta media is an efficient medium for acquiring Arabic language.